TAYANGAN DAKWAH DAN LAHIRNYA DA’I SELEBRITI - Dawud (Al'Adalah, 2015)
Modern information technology has changed a lot of things in the current social of life, no exception public religious life. The model further islamic science transmission is strongly influenced by the development of information technology and communication. During the preparatory phase of manuscripts, printing stage and phase television and computer exhibiting a different about the image of Ulama and da’i. The da’i and Ulama who promoted by media seem challenging and shift authority traditional Ulama. The emergence of da’i-selebrity is consequence of strong domination of television .The ability of television change reality become hiperreality bring up a new culture that Baudrillard called as Simulational culture. In the field of religious, simulation culture it bore new religious authority , namely da’i-celebrity who usually invoked ustadh. The arrival of new religious authority by television production is challenging religious authority old and given to talking about Islam in the public. Ulama which were determined by it’s mastery over the sciences of classical subjects now melting with with young da’i, fresh , and in new produced and reproductive by the television media. No more the boundary between real ulama and hyperreal ulama who produced by television.